2003
DOI: 10.1081/ja-120017385
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and Substance Misuse: A Tale of Two Cities

Abstract: In this article we examine the relationship between alcohol and drug misuse among the literally homeless (those living out of doors and in emergency shelters) in Hartford, Connecticut and Providence, Rhode Island, two northeastern U.S. cities of comparable size. We worked with homeless advocacy organizations in both cities, using a point-in-time census (N = 1058) and random sample (N = 66) in Hartford, and a sampling of clients (N = 82) of six shelters serving residents of Providence (N = 82). We found substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Thus, homeless individuals must turn to service providers to meet their basic needs rather than on treatment for the substance abuse problems. The irony is, however, that many of these providers must work within budget constraints that do not allow them to treat the problems that may have contributed to the homelessness in the first place or that may prohibit the individual from overcoming the homelessness (Glasser & Zywiak, 2003). Yet, while Hartman (2000) notes that substance misuse and mental illness are often thought to lead to homelessness, they are not the root cause of homelessness.…”
Section: T L Dietzmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, homeless individuals must turn to service providers to meet their basic needs rather than on treatment for the substance abuse problems. The irony is, however, that many of these providers must work within budget constraints that do not allow them to treat the problems that may have contributed to the homelessness in the first place or that may prohibit the individual from overcoming the homelessness (Glasser & Zywiak, 2003). Yet, while Hartman (2000) notes that substance misuse and mental illness are often thought to lead to homelessness, they are not the root cause of homelessness.…”
Section: T L Dietzmentioning
confidence: 98%
“…It is estimated that between 20% and 80% of the homeless population has some form of substance abuse problem (Hartwell, 2003), and it is believed that prevalence of substance misuse is higher among the homeless. Indeed, the connection between substance abuse and homelessness is so pervasive that in some cultures, the words are the same (Glasser & Zywiak, 2003). Furthermore, Johnson, Freels, Parsons, and VanGreest (1997) concluded that drug use was one of the most important risk factors for the first episode of homelessness.…”
Section: T L Dietzmentioning
confidence: 98%
“…It is estimated that between 20 and 80% of the homeless population have some form of substance use-related problem (Hartwell, 2003). Indeed, the connection between substance use and homelessness is so pervasive that in some cultures, the words are the same (Glasser and Zywiak, 2003). Furthermore, in a 1997 study of a sample of homeless and at-risk for homeless, Johnson and colleagues (Johnson, Freels, Parsons, and VanGreest, 1997) concluded that drug use was found to be one of the most important risk factors for the first episode of homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Using a simple random sampling approach, Glaser and Zywiak (2003) sought to better understand the role of alcohol and drug misuse among persons who are homeless. The accessible population to the researchers included those who were accessing homeless services in two cities in the Northeast United States.…”
Section: Simple Random Samplingmentioning
confidence: 99%